Early saccades in amyotrophic lateral sclerosis. Issue 4 (May 2013) - Burrell, James R.; Carpenter, Roger H. S.; Hodges, John R.; Kiernan, Matthew C.
Abstract: Our objective was to correlate saccadic abnormalities, including early saccades, in patients with amyotrophic lateral sclerosis (ALS) with measures of motor and functional impairment. A portable saccadometer was used to record saccades in ALS patients and control subjects. The linear approach to threshold with ergodic rate model was used to characterize saccades, including sub-populations of early saccades. Patients with established cognitive impairment or frontotemporal dementia were excluded. Limb-onset (Limb ALS) and bulbar-onset (Bulbar ALS) patient groups were compared and saccadic abnormalities were correlated with measures of motor and functional impairment. In total, 48 participants were included in the study; 24 patients with ALS (15 males, 9 females; mean age 57.0 +/− 13.9 years; mean symptom duration 22.4 +/− 16.3 months, of whom 62.5% had Limb ALS) and 24 age-matched controls. Early saccades were increased in both Limb ALS and Bulbar ALS patients, but other saccadic parameters were normal in ALS. Saccadic abnormalities did not correlate with motor or functional impairment. In conclusion, ALS patients show increased early saccades, but exhibit no significant differences across ALS phenotypes.